2003
DOI: 10.1046/j.1365-3024.2003.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Lafoensia pacari extract inhibits IL‐5 production in toxocariasis

Abstract: Toxocariasis is an infection induced by Toxocara canis, an intestinal parasite of dogs. In this study, an experimental murine model of toxocariasis was used to evaluate the anti-inflammatory activity of an ethanolic extract of Lafoensia pacari stem bark. Mice infected with T. canis were treated with L. pacari extract (200 mg/kg, p.o.). Subsequently, we observed a reduction in the number of eosinophils in the peritoneal cavity, bronchoalveolar fluid, blood and bone marrow. Production of interleukin (IL)-5, a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 32 publications
4
29
0
2
Order By: Relevance
“…The macerate prepared from the stem bark is a popular remedy for the treatment of wound healing, fever, gastric ulcer, gastritis, utero inflammation and upheavals of biliary vesicle (Guarim Neto & Moraes, 2003). Previous works have shown that Lafoensia pacari stem bark ethanol and methanol extracts possess anti-ulcer (Tamashiro-Filho, 1999), anti-inflammatory (Albuquerque, 1996a, Rogerio et al, 2008a), immunostimulating (Albuquerque, 1996b, free radicals scavenging (Solon et al, 2000), antiviral (Müller et al, 2007), anti-eosinophilic (Rogerio et al, 2008b), analgesic and anti-oedematous (Rogerio et al, 2006) and inhibition of interleukin (IL)-5 production (Rogerio et al, 2003) activities. According to Solon (1999), this plant is rich in ellagic acid, which presents gastric anti-secretory (Murakami et al, 1991) and antibacterial effects (Chung, 1998;Lima et al, 2006) and a recent clinical study carried out with Lafoensia pacari extract revealed positive effects on the symptomatology of Helicobacter pylori infected patients (Mota Menezes et al, 2006), but to the best of our knowledge, there was no published report on the plant's antifungal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The macerate prepared from the stem bark is a popular remedy for the treatment of wound healing, fever, gastric ulcer, gastritis, utero inflammation and upheavals of biliary vesicle (Guarim Neto & Moraes, 2003). Previous works have shown that Lafoensia pacari stem bark ethanol and methanol extracts possess anti-ulcer (Tamashiro-Filho, 1999), anti-inflammatory (Albuquerque, 1996a, Rogerio et al, 2008a), immunostimulating (Albuquerque, 1996b, free radicals scavenging (Solon et al, 2000), antiviral (Müller et al, 2007), anti-eosinophilic (Rogerio et al, 2008b), analgesic and anti-oedematous (Rogerio et al, 2006) and inhibition of interleukin (IL)-5 production (Rogerio et al, 2003) activities. According to Solon (1999), this plant is rich in ellagic acid, which presents gastric anti-secretory (Murakami et al, 1991) and antibacterial effects (Chung, 1998;Lima et al, 2006) and a recent clinical study carried out with Lafoensia pacari extract revealed positive effects on the symptomatology of Helicobacter pylori infected patients (Mota Menezes et al, 2006), but to the best of our knowledge, there was no published report on the plant's antifungal properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in the activation of mature eosinophils, IL-5 is the principal Th2 cytokine involved in terminal differentiation and proliferation of eosinophil precursors [3,4]. Furthermore, IL-5 is essential for eosinophil migration from the bone marrow into the blood [5,6].Pharmacologic compounds capable of inhibiting eosinophil function or infi ltration are desirable for the treatment of patients with atopy/allergic disorders, hypereosinophilic syndromes, and other eosinophil-related diseases. A number of novel classes of drugs that inhibit eosinophil activation are currently under development, suggesting that there are different therapeutic targets, most of which are suppressed by corticosteroids.…”
mentioning
confidence: 99%
“…In addition to its role in the activation of mature eosinophils, IL-5 is the principal Th2 cytokine involved in terminal differentiation and proliferation of eosinophil precursors [3,4]. Furthermore, IL-5 is essential for eosinophil migration from the bone marrow into the blood [5,6].…”
mentioning
confidence: 99%
“…Em estudos prévios utilizando ratos infectados com parasitas intestinais, a fração aquosa do extrato etanólico das folhas de L. pacari foi capaz de diminuir signifi cativamente o recrutamento de eosinófi los. Em um modelo de peritonite aguda induzida por -glucana, o extrato etanólico de mangava brava apresentou um efeito antiinfl amatório, sendo a atividade atribuída à presença de ácido elágico (7) (Rogerio et al, 2003). Um estudo mais recente utilizando um modelo experimental clássico de asma induzida por ovalbumina mostrou que tanto o extrato etanólico das cascas dos caules de L. pacari quanto o ácido elágico foram capazes de diminuir o número de neutrófi los e eosinófi los no lavado broncoalveolar e no parênquima pulmonar (Rogerio et al, 2007).…”
Section: Derivados De áCido Cinâmico E áCido Benzóicounclassified